2008
DOI: 10.1007/s00134-008-1091-y
|View full text |Cite
|
Sign up to set email alerts
|

Computer-assisted glucose control in critically ill patients

Abstract: Objective: Intensive insulin therapy is associated with the risk of hypoglycemia and increased costs of material and personnel. We therefore evaluated the safety and efficiency of a computer-assisted glucose control protocol in a large population of critically ill patients. Design and setting: Observational cohort study in three intensive care units (32 beds) in a 1,300-bed university teaching hospital. Patients: All 2,800 patients admitted to the surgical, neurosurgical, and cardiothoracic units; the study pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 31 publications
1
73
0
4
Order By: Relevance
“…[18][19][20][21][22][23]26 These have revealed less hypoglycemia and improved adherence to the protocol. Other studies have demonstrated that even experienced clinicians following complex paper protocols often make critical mistakes that lead to unwarranted hypo-or hyperglycemic excursions.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…[18][19][20][21][22][23]26 These have revealed less hypoglycemia and improved adherence to the protocol. Other studies have demonstrated that even experienced clinicians following complex paper protocols often make critical mistakes that lead to unwarranted hypo-or hyperglycemic excursions.…”
Section: Discussionmentioning
confidence: 92%
“…[13][14][15][16][17][18][19] Several investigations have demonstrated that automation of ''paper'' protocols via insulin-dosing calculators can enhance compliance, reduce errors, and improve glucose control. [18][19][20][21][22][23] In the original Yale protocol articles, adherence to the published algorithm was not assessed. Accordingly, its reported metrics of glycemic control could never be assessed in the context of how precisely the protocol was actually followed.…”
Section: Introductionmentioning
confidence: 99%
“…Development of CGM technology 74,77 is underway to provide realtime near-continuous BG quantification, minimizing a concomitant increase in nursing workload requirements. 78 Several CDSS applications for insulin management are currently commercially available, [79][80][81][82] demonstrating reduced glycemic excursion and significantly fewer hypoglycemic events.…”
Section: Glycemic Control Challengesmentioning
confidence: 99%
“…At the same time, it reduces nursing workload, thereby improving efficacy and safety. [8][9][10][11] To our knowledge there is no evidence of these improvements in an internal medicine setting. This, Article in spite of the lack of appropriate nursing resources being the main limitation on the use of intravenous insulin protocols, which are therefore underused.…”
Section: Introductionmentioning
confidence: 97%